Qur’ānic exegesis in Malaysia: general overview with special reference to the recent development - Fadzil, Ammar; Ahmad, Nadzrah; Ahmed Ali, Ahmed El-Mogtaba Bannga (IIUM Press, International Islamic University Malaysia, 2018)
This paper discusses the general historical development of Qur’ānic exegesis in Malaysia since its independence until today via two perspectives, namely the historical development of Qur’ānic exegesis and recent improvements of Qur’ānic exegesis. It applies two methodologies, historical to collect relevant data and analysis to scrutinize the collected data. The paper concludes that the Qur’ānic exegesis in Malaysia owes its birth and development from earlier Muslim exegesis, particularly those written in Arabic. The contributions of Indonesian scholars has continued until today through writings and public lectures. Although most of the work is primarily translations which developed from prior exegetical pioneers, they offered innovative additions especially through tafsīrs that apply a more wholesome societal approach.